Genocide in the modern age : state-society relations in the making of mass political violence - Karazsia, Zachary A. (Routledge, 2025)
This book explores why some episodes of mass political violence and genocide are so much deadlier than others and under what conditions perpetrators in government and society opt for brutality as a means of accomplishing their goals. Introducing the new concept of "mass political violence" to explain genocide and other mass killings in the modern world, the author investigates "how" perpetrators sustain the capacity to enact violence on a large-scale, irrespective of motives. Cases including the Holocaust, Soviet Union, Rwanda, Cambodia, the Lord's Resistance Army, the Islamic State, the Ottoman Empire of the 1890s, Mao Zedong's revolutionary violence, the Congo Crisis, and Darfur are used by the author to identify four types of mass political violence perpetrators - state actors, state-society coalitions, state-sponsored groups, and non-state actors to explain historical trends and identify which perpetrators are most likely to emerge in a given socio-political context and sustain violence over time. Comparative and grounded in case studies, this book will interest policymakers, diplomats, governmental advisers, practitioners, and industry researchers. It will also be invaluable to students and scholars of Political Science, International Affairs, Holocaust and Genocide Studies, Human Rights, Sociology, Anthropology, Geography, Political Psychology, Religious Studies, Gender Studies, Public Policy, Media Studies, and Criminology.
Keywords: Genocide -- Case studies.; Political violence -- Case studies.; elektronické knihy; electronic books